Future urban habitation transdisciplinary perspectives, conceptions, and designs - Heckmann, Oliver,|d 1974-; Siew, Man Kok (Wiley Blackwell, 2022)
Around the globe, urban populations are growing at an unpreceded rate, in particular in Asia and Africa. In view of pressing social and environmental challenges it is essential to reimagine current design strategies to build affordable, sustainable, and inclusive communities that can respond to future demographic dynamics, new social practices, and the consequences of climate change. Future Urban Habitation presents an integrative, transdisciplinary approach for developing long-term strategies for urban housing at a different scales. With focus on the rapidly growing cities of Asia, and urban processes in Europe and North-America this volume offers perspectives from both researchers and practitioners involved in multiple aspects of urban habitation. The authors address a range of challenges to urban habitation with four intersecting thematic frameworks: Inclusive Urbanism, High-Dense Typologies for Building Community, Adaptable and Responsive Habitation, and New Tools and Approaches.